The exocrine glands of swarming females and physogastric queens of Cornitermes cumulans (Kollar) (Isoptera, Termitidae, Nasutitermitinae) - Ignatti, Ana Cristina [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Sociedade Brasileira de Zoologia, 2001)
The histological study of the exocrine glands in the swarming females showed the presence of tergal glands, mandibular glands, salivary glands and sternal glands. Tergal and sternal glands are not developed in the physogastric queens, probably, because of a regression process. The development of mandibular glands is similar in swarming females and physogastric queens.
Keywords: Isoptera; glandular system; exocrine glands; histology; physogastric queens; termite